Closure of Abdominal Defect by using Native Detrusor Muscle for Bladder Exstrophy (Bangladesh Journal of Urology, 2012)
Bladder exstrophy is a congenital anomaly that has been little bit difficult to correct. Advances in reconstructive surgery, have impacted on the care of these patients. The ideal reconstruction is directed to accomplish closure of the abdominal wall and bladder with subsequent correction of reflux, bladder neck revision for continence, and anatomical and functional repair of the epispadias. External and internal diversion may still be required for classical exstrophy when the bladder is represented by a fibrous patch and other complicating anomalies prevent closure or subsequent growth of the bladder.In such case, repair of anterior abdominal wall defect is also challenge. We present here a case where we used the native detrusor muscle of the patient after stripping off its mucosa to cover the muscular defect in the lower abdomen, and then the wound was covered by using local skin flaps. Bangladesh Journal of Urology, Vol. 14, No. 1, January 2011 p.19-21